The generous bestower The beautiful names of God - Ergun, Erol; Egitim, Hasan (United States of America Tughra Books, 2011)
Feathers loved to fly, exploring the magnificent work of art exhibited before his eyes from high in the sky. The flowers of all colors, the green grass spread over the hills and meadows, the bright blue sky, and the shimmering lake at a distance...As he was gazing at this vast and breathtaking scenery, he was immersed in thought. (3z(BEverything on the Earth seems to be competing to show God$1 (Bs excellent art,(3y (Bhe thought. Then he stylishly glided downwards to attend one of the regular meetings at the lakeside. Let$1 (Bs join their meetings and see how all of nature is busy striving to reflect the Beautiful Names of God.s